Alternative Ways to Improve Green Design in Sport Complex, Universiti Utara Malaysia - Sabar, Rohafiz; Anuar, Nur Khairiel; Ahmad, Za'im (2020)
Green design integrates modern society become more efficiently and healthy. Designers, developers and builders consider alternative resource such as renewal energy and green technology to construct new building or convert existing buildings into green building. The quality and availability, incentive, education and government policy and regulation of implementation of green are recommended. The purpose of the paper is to evaluate the awareness of green surface access on sport complex in UUM and the importance of green building application to the public. The research explores the user preferences that may change the future pedestrian design. The impact of this study might useful as a theoretical guideline for road planners to design a new pedestrian pathway in UUM areas by considering the preferences of facilities needed. Although a number of papers have been written on pedestrian facilities in general, a detailed evaluation of current provision of pedestrian facilities and the importance of future provision of pedestrian facilities as well as an expectation of transport users as original research is regarded as adequate for the purpose of this research. The research contributes to increase the pedestrian protection system and safety as campaign and road safety education. Thus, this research explores the preferences of pedestrian facilities may change the future pedestrian design in Sport Complex areas based on provision of pedestrians’ perception. In addition, the results of the study might useful as a theoretical guideline for road planners to design a new pedestrian pathway by considering the preferences of facilities needed